Informal economic activities at the borders: balancing well-being and Nusantara development - Zaini Othman,; Kartini Aboo Talib @ Khalid,; Zarina Othman, (Penerbit UKM, 2024)
Nusantara, a newly established metropolis in East Borneo, aspires to facilitate connections between the region of Kalimantan and neighbouring states such as Sabah, Sarawak and the Philippines by deploying advanced technology and infrastructure. Even with substantial investments aimed at modernizing Kalimantan, indigenous subethnic communities residing along Sarawak and Kalimantan’s borders persist in engaging with traditional informal economic activities, particularly at the confluence of these regions. This paper investigates the prevalence and significance of barter systems and the exchange of goods, including certain commodities frequently classified as illegal under specific regulatory frameworks. While several of these activities may encompass smuggling elements, they do not involve illicit items such as narcotics, weapons or human trafficking, thereby necessitating a re-evaluation of security and safety considerations in the area. Through narrative interviews conducted with five prominent leaders from border communities representing diverse cultural and social backgrounds, alongside non-participant observations of local practices, this study examines the contribution of informal economic activities to these border communities’ stability and ecological balance. The findings challenge prevailing perceptions that categorize these activities as a mere grey area phenomenon, revealing their crucial role in fostering mutual benefits, establishing familial trust and enhancing collective tolerance. These informal exchanges are vital for the community’s survival, illustrating a complex social and economic interdependence web. This research offers essential insights into the dynamics of informal economies within border regions, underscoring their often-neglected role in fostering social cohesion and resilience. By providing practical implications for policy development and community relations, this study contributes to a more comprehensive understanding of the interplay between informal economic activities and regional stability.